Screening cellulolytic fungi isolated from Malaysia cocoa pod husk and its culture conditions for cellulases production - Jimat, Dzun Noraini; Azmi, Azlin Suhaida; Ahmad Raus, Raha; Talha, Nur Syakirah (Faculty of Agro based Industry (FIAT), Universiti Malaysia Kelantan (UMK), 2015)
The aim of this study was to screen few fungal isolates from local cocoa pod husks (CPH) which able to secrete cellulases. The isolates were plated on carboxymethyl cellulose (CMC) agar plates which then incubated for two days at 28ºC. Then, these plates were stained with congo red dye for 0.5-1 h followed by destaining with 1 M NaCl solution for 15-20 minutes to observe its cellulolytic activity. One isolates which exposed the largest cellulolytic zone on CMC agar plate was selected for further study. In this study, culture conditions with respect to pH, incubation time, amount of substrate (CPH) and temperature were screened using Design expert version 8.0 by employing two-level factorial design. The selected fungus isolate was cultured in shake flask at 37°C with agitation of 200 rpm for 5 days in incubator shaker. During fermentation period, samples were collected every day for fungal-cellulases activity of filter paper activity (FPase) and carboxymethyl cellulase (CMCase) activity. Analysis of variance (ANOVA) of this study showed that the most significant parameters that affects the production of cellulases from the selected fungi isolates were the amount of substrate (CPH) used followed by the interaction of amount of substrate with pH (p< 0.05). It showed that the cellulases activity was high when the pH 9 with more amount of substrate used. However, it was observed that less significant changes of celllulases activity when different amount of substrate was used at same pH of 3. Based on the microscopic observation of isolate, its morphology was closed to Rhizopus sp.. Further study is essential to optimize the selected culture parameters obtained in this study in order to maximize the activity of cellulases from the selected isolates.